PRODUKTIFITAS KERJA SELAMA PANDEMI COVID DENGAN MENERAPKAN WORK FROM HOME BAGI PEKERJA WANITA - Peni Jaelani, Agus; Sutrisna, Arga; Putri Lestari, Suci (JURNAL EKONOMI PERJUANGAN, 2024)
This research aims to find out how female employees work productively during the Covid pandemic, when companies implemented work from home for female employees in Tasikmalaya City. Primary data was taken by distributing questionnaires to female employees in the city of Tasikmalaya. The research sample was determined using the Accidental Sampling technique by distributing questionnaires in the form of a Google Form. data were analyzed using the PLS-based Structural Equation Model method. From this research, it is known that the work performance of women who work at home to complete housework tends to decline further due to disruption of the housewife's duties. Where they have to work multitasking, this is aimed at negative results from the relationship between WFH and WLB to increase performance. work whose results are not significant, so WFH is not suitable for married female employees.   Keywords: work-life balance, achievement, working from home